Pengaruh Women on Board of Commisioner, Women on Board of Director, Sales Growth dan Board Size, terhadap Financial Distress - Ohandi, Jenifer Fitriani; Puspitasari, Windhy (BUDGETING : Journal of Business, Management and Accounting, 2024)
This research aims to determine the condition of financial distress and how women on the Board of Commissioners, Women on the Board of Directors, Sales Growth and Board Size influence financial distress using the Altman Z-Score analysis model. The population studied came from the LQ45 company listed on the Indonesia Stock Exchange (BEI) in the 2018-2022 period and samples were taken using a purposive sampling method so that the total number of data studied was 92 samples. This data is taken from the company's financial reports and annual reports which are availableon the BEl website or each company's website. There were several tests carried out inthis research. namely the normality test. classical assumption deviation test, and hypothesis testing. The results of this test show that Women on the Board of Commissioners have no effect on Financial Distress, then Women on the Board of Directors have a positive effect on Financial Distress, while Sales Growth has no effect on Financial Distress and Board Size has a positive effect on Financial Distress. Keywords: Financial Distress, Sales Growth dan Board Size, Women on Board of Commissioner, Women on Board of Director.